Representation of Gender Roles in the Choreography of Rantak Nagari Parampuan within Minangkabau Matrilineal Society - Emri Emri; Susas Rita Loravianti; M Halim (Pascasarjana Institut Seni Indonesia Padang Panjang, 2026)
This practice-led study examines the choreography Rantak Nagari Parampuan, presented at the 2024 Alek Mandeh Festival in the Sijunjung Traditional Village, as an artistic articulation of changing gender roles within Minangkabau matrilineal society. Previous discussions of Minangkabau women frequently emphasize normative status, customary authority, and the ideal figure of Bundo Kanduang, while fewer studies explain how contemporary choreography transforms tensions between domestic, cultural, professional, and public responsibilities into embodied performance. The study aims to identify the creative process, performance structure, and cultural meanings through which the work negotiates those multiple roles. Data were derived from field observation, discussions with local community members, rehearsal documentation, choreographic notes, and reflective evaluation of the performance process. The creation process followed the stages of exploration, improvisation, formation, and evaluation adapted from Alma M. Hawkins. The findings show that the work is organized into six dramaturgical sections: religious and moral education, domestic labor, social interaction, participation in communal activities, contemporary female identity, and the adaptive position of men in a matrilineal kinship system. Movement, vocal sound, musical accompaniment, and ensemble composition construct the idea of rantak as grounding, awareness, balance, and resilience. The work does not merely celebrate women’s customary position; it stages negotiation between inherited cultural obligations and contemporary social mobility. This study contributes to dance creation research by demonstrating how matrilineal values can function as both thematic material and a dramaturgical framework. Its novelty lies in reading the choreography as a relational representation of women and men rather than as a singular glorification of the Bundo Kanduang figure.